Primary plasma cell leukemia presented as progressive paraplegia: a case report - Hasmoni, Mohamed Hadzri; Abdul Wahid, Fadilah; Cheong, Soon Keng (Southern Medical Association, 2009)
Plasma cell leukemia (PCL) is a rare plasma cell disorder. It is the leukemic variant of multiple myeloma. A 52-year-old man with an atypical presentation of primary plasma cell leukemia is reported. The patient presented with paraparesis which progressively worsened to paraplegia. MRI of the spine showed an extradural mass causing cord compression and multiple bony erosions from soft tissue masses. Peripheral blood film examination and bone marrow aspiration showed numerous plasmablasts. Atypical cells expressed surface and cytoplasmic lambda light chain on immunochemical studies, surface CD45 and CD38. To our knowledge, primary PCL presenting with progressive paraplegia has not been reported in the literature.